Glucose 6 phosphate dehydrogenase deficiency among neonates with hyperbilirubinaemia in western Iraq - Al-Hiali, Sahar J (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Glucose -6-phosphate (G6PD) deficiency seems to be a major cause of neonatal hyperbilirubinaemia. This study was carried out to determine the prevalence of G6PD deficiency among icteric neonates in western Iraq and to evaluate its association with hemolysis in neonatal jaundice. Patients and Methods: All icteric neonates admitted to Al-Ramadi Maternity and Paediatrics hospital, Al-Anbar governorat, for the period from 1st Feb. to 1st Dec. 2006 were included in the study. Data collected from case records and includes age, sex, total serum bilirubin hemoglobin level, reticulocyte count, blood group and Rh of the mothers and neonates, direct coomb’s test and peripheral smear. G6PD enzymewas measured also. Results: eight out of 100 icteric neonates had G6PD deficiency, with male to female ratio of 7:1. A significant higher total serum bilrubin (TSB) level was among G6PD deficient icteric neonates than that among non deficient icteric neonates. Reticulocytes count and haemoglobin level was not significantly differ between G6PD deficient and non deficient icteric neonates. Conclusion: Neonatal screening for G6PD deficiency is a need in order to control genetic blood diseases.